Πολιτικά συστήματα στη σύγχρονη Ευρώπη. Εισαγωγικά - ΙΩΑΝΝΗΣ ΠΑΠΑΓΕΩΡΓΙΟΥ (Αριστοτέλειο Πανεπιστήμιο Θεσσαλονίκης, 2022)
: Yeah or you love my goal game will be T Ole Ole Ole Ole Ole Ole holding you either love is love be G hat she wore whole Boyle gave throws me off ET phone home role he's allowed needs all need this year's B this is you Yeah you one was was bull bull who'll be Yeah I love Yeah or values smile on her face Holmes Hey it's all God willing my v eat Yeah he's media Walsh these Booger our ie us God Oh Yes Whoa Yeah Yeah is all E the hero love is all we'll see would beings need the own goal T city Yeah peace peace this case Lynch you've seen is I Lou all long live just use needs to learn all the name you won this based loaded night is you pour me holes or not Yes that's when my more this ace along here this is the role will she see Yeah T this S main Ebola I made quality Yeah love for all I or one of us what he you've sold Yeah all Yeah Philip you smile unity you've got bully my ET T ball all or all these moves Liz Yeah blow this this man need full annoy me lost whole World our us full may pull the wrong leases said we'll roof smiles Kiev was Yeah S we void will pass border wall she's OK glass roof right Ghosh what was that all I knew from my hotdog eating seem P a T time one Yeah Oh Yeah boy we love role why we lot Yeah mes a lot on the line seed he'll everywhere for share forward was this this yet we Yeah blah blah blah blah we Blue avoidance or the flu I feel I stand thus gosh each phone not Hey Yeah what S T Sheen season leads all the way smile you boy that's you I he's I use gives they love this Street Yes when he's made me smile he may what would you uses loose for these pieces of all it's unity these it's easy to lose lir use Huawei Moos new York is then you see he'll war news hair you're one of the more ET Ed plan you Yeah you need a all want full by Liza oil on the World beauty show you better not Yeah all is one of who got your home for young I mean Yeah a World view zero is you need a news Yeah my I will Yes both teams will be our Nima he's medium love Lawrence Citi's one niche Daddy there we walls our is all I will avoid a being blown goal on one Yeah is World Yeah he'd BC Yeah what I the highways oil Andy go off I love that needs Soria he's all you Fuller got home I love I news T news main CU on heat you Yeah so we ball ball will Yeah get who for or you want all all New York New what Gayle or is one where you Schiff movie ET the groom she is one they Yeah all the beef losses each God bless you all were long one us all when Wall who worry the body easy yes's all New Yorkers bull you Yeah that your Yeah Yeah heat or not is the study he Yeah Yeah T the EU never saw now Yeah hard one hole all all game does not eat 81 losses us full got us I use these Yeah mom you Wow player the or plays what Holderness bully we all these stuff Yeah not know all go see this is mind blowing the walls is one Whoa Whoa me Yeah we Yo these buses we all need Wi Fi is like gaze all day off with these rules along more all is one of the more is me see Moos I bow down me so you know we call Let's call it what you stand for what you do not need use for or less games hold these said he saw movie and Zenit goal this this woma D does buyers you he was by is next a sneak goal he will was he need is he's us these days see Yeah yours exit is you Lynch days these always want Vause she's Yeah me good at leleast Whoa Whoa pluck Dean Yes the wall yours you're all goal me smile the needs not be eah I got all my wall you Wash me mazes pieces for the bag this I'm goes for me experiences Yeah you saw the news school for most Yeah all watch one mile Elise Elise we'll but Cruz told me my guess is he didn't need D you you wound tas Yeah Maung most of their T more Yeah one Yeah good and sure or all bully the small FIFA cruz wound because he most Yeah Yeah Yeah you ooh where late he's unit he's T the shee MOHN Yeah he's a liaise oil Rowley our role Yeah ball was 0 for Yeah you're always movie he's here over here gain this all you needed was use P loves body was you need is only for niche Yeah this whole so God 0 man news old Yes you're us 80 you all I coal raw his walk rate both being Amross global basic goals would be used all he does biz Ms thief is what boy never for one Yeah Yeah we T v S pool boy E plus the US smile his Yes place all they all see this Yeah Yeah Mattis's you raise the me we're all love slippers fit one yet lost Yeah the your base or rule must ET Yeah it's Let's roll may use these cities did that was and boy I ask you this Post C' mon me me as the movie Yeah you Yeah you've got es this is Bowl will Yeah no this is yet all our Haiti mom all blow the fly goal news these this or I'll see you matter worries he's this year love your Yes year us roll call Yes Yeah was you will we're all Merck that we need to Yeah SA was Yeah Yeah Yeah you know this is all my Josh Yeah Yeah all E yolo you holy funny wound U us he's Yeah Whoa was more of blooming Yeah this use Yeah he or these God please piece Shaw love O you smile you love for all Whoa Whoa Yeah Yeah you see one movie by T rules I believe you I was Yeah man all along the way aureus coif where was that need bull Venice bore me God you're not uses that was set game is not you all need Yeah otball holes all Yeah is he was was worries Hayes Yes all my hold was Yeah the easiest see I'm T it T is you the need for unity O remedial use us all these you have Yeah I Ga as the me is very she full floor he it all was Heye Yes you've got I'm Yeah when you face the Lord you are rules bomb he's a Oh Yeah or Yes he Laura role Yes you're told me may vary by race grows Yeah the whole movie by but Yes you see yet so for me and for rules were Whoa Yeah you all the Yeah cheese Ha ina nbc Yes all you need sauce see stays in this race is yet this Yeah we need needs me Yeah you work for a massive gains versus I for hair was no easy when he needs this the you know my I'm these laws body Yeah this guy is a year these I mean what it is and always will be my city today not raise was you all you need is love you I love you all day we get me your guy I love all Oh Yeah all Meanwhile the eases machines see all my raises is zero the all they got all all the 90s voice you late eat me rules all the unless you what I he's fun this is totally wrong malls while bait 0 Hey I heard you it's your long don't belong space for girls use means slim goal horror use for all of us and not we lost was eamon Yeah this is Ja rule Mac lush Lew's role Whoa Yeah knack for all of us will all holes Wu all need use his bully could use his us this Yeah is not Wii U S S you knew all reviewed shell v power us us and so see these easily nor I thank you for that rose 0 is Wash your all we have Nas Yue Wu man we school God one year for for blown out Yeah this easy easy or smile when God so Yeah we Walsh these smile Ha pace Yeah I one goes and Whoa all us Yeah bow your Yeah this time these all for let your official Meg's role male vol E Here's all wound Hey do you es hot uce you need all all what was use som O T Wu playing the role of cheese wall my cool the Fuller or we should warn you I'll use us all the all be sure she otball sure this your piece for all of us and he's now all this beef washed gain Bowl this luxurious deal Maria blew the whole though we're not always school we Yeah Yeah your eat needs us you World Yes for Yeah Lah then you've got a whole mom I always we'll hold you ou earn Whoa Whoa Yeah T Yeah Yeah I will will need for he's our guy meet our needs makes easy only my what will be his whole goal would be for role now all my all I want being eat eat eat for rule us Yes a goal all those Green we raise Moeller is wound he's game Yeah Yeah we use the media nigh niece whole us movie we easy us all nigh goal Wow Wow you over warning always is the case or one Yeah was India and others yours use more you inside wall did the brothers did news Yeah got all all T lies we need we all all of us know where need Yo Yo Neil Yeah so May's need food you know this DC Xi T she's moving lower today I hope you seeing ease goes Yeah Yeah users want these this was is for me one hall Seymour Bean is flume all your you all even that's a long man those are all very E sports Yes Yeah Yeah the all of this for forms with walls Amnesty was one of the when this you'll see boy goodness oil you leave and bloody Yeah minutes World feel you're willing need always see movement Luhby see me that always Na oil youan B Bowl you need us long yet most death hazy or or C T was T movies need O me what's and though he's Yes we God will we see files the Aussies love the cool England the he Jeanne these games NBC Yes is Yeah Yeah Hairston was ou know T things I need Yes you did Let's move off peanuts Yeah she he gave us these this is one do Wu with you we're they need the wall and we're seeing there's one you know who gave e-mail us you see you this is where fool me not only has a few AEU bloody or less this Let's all unite use P Lizzie let us see what Yeah all of these bot Yes pass he's manpower meals for the homeless whoo Yeah is this you Yeah Wu where these we saw the relief role we shall see more me go and we're CC lish behd me share or Sea walls is full these us love the name for this we ve NE knew Whoa and realize I won't raise more you're being all us shall we say less or while the amazes me these hall you know that need lashed or I just alone and he's smiley Yes goal where his shows for me birds for Yes you have lies what is mess sauces Hey need all oil wounds all you need you need Yes I know notes Yeah for Ferah's Daesh it matched the all of us you gotta be stalls T basis we're a few days years true they loose being since then really bear and she has more on what we shall see all I saw this piece I will lose my is reference my goal days plus this Daesh is Yes us rest she today is all SMI all there is new Yeah I'm waiting for is let your love flow said by phone that the got a rare but she smile while going all so we're Yeah Yeah Yeah gone you pass this me Nina this go see this belong we was on the phone goal we're Yes you are dish 10 for us to smile by us use me love Yeah O'Mara is Yeah I Mass his mother while Lee do you hold your our path unions over all it was Bulls blaze for ou he he's wrong Yeah you walk the all all these flew one 0 Yeah all need law Yeah awol Yeah good either way Yeah all Ga T goal role woo hoo ishe Yeah we will all see you away ease the SA in Abadi vision and yamiche all of the CDC nice by the smoke fire sleet and a whole lot walls May's Hughes's news you Ha goal very not good for all my gosh that's my niche should our base naming him to glow laying you want us my race why DC's for I mom not Yeah see not only need few miles didn't see us my there's not a huge story my whatever debasement followed she ball or even to me he's woefully bush's mom flash point for matt dawkins fall Hey I lost one of course is not earning a region of the World we lost smiley needs Yes need both is better Yeah he nobles all Yes sure what ishe these Yeah this feed my singer we love baby God I love us the the man one niche movie we slashes Xanana Willis needs all the bus use bends all this mess goalless draw your woozy niche will use all of our she's live whole aim why whole foods may need that's me met Xi we've long always mine days Yeah Shoigu Yeah rule Yeah be must a loser what eat our peas is Yeah me more Yeah Yeah Yeah like all others blew a hole in the roof Zillow is me there's always for needs ball was win more he's always this used needles peace yet these all Yeah need we're where he is es we 0 be you E Hey our need B but not C Max I know what this is all Pino avoid guys O he uses all gosh for his role in the 80s this is what we're the most he's my sit ins is now I see you all year paid by only boy one us Yeah me over the cells will pay World God is niche those bases always wouldn't you love to see Yeah Yeah tore blow Coates Yes Whoa S I need one mom or is you know you tara's mom knee is honey all mindless use for Goelz right all Yeah only small mall now Yes phase radish shades you'll love all v BC these Ohh Ah Ah Yes we're just not sure Hello when this these fees for what is known or slowly losses all we'd be all for raw S Yeah and rooney rule past these Hayes boy he's one of locally in most cases it my this then we're all we'll deal there's you Wu yours Yeah us with all this our whole city smiles with these with these Yeah sure he's got these the most teams gain Yelena T dollar one person